2020
DOI: 10.7150/ijbs.45420
|View full text |Cite
|
Sign up to set email alerts
|

How DNA methylation affects the Warburg effect

Abstract: Significant enhancement of the glycolysis pathway is a major feature of tumor cells, even in the presence of abundant oxygen; this enhancement is known as the Warburg effect, and also called aerobic glycolysis. The Warburg effect was discovered nearly a hundred years ago, but its specific mechanism remains difficult to explain. DNA methylation is considered to be a potential trigger for the Warburg effect, as the two processes have many overlapping links during tumorigenesis. Based on a widely recognized poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 153 publications
0
27
0
Order By: Relevance
“…Since tumor cells produce energy through aerobic glycolysis (Warburg Effect) under hypoxia condition 12 , 13 , we examined the levels of pyruvate and lactate, the metabolites of glycolysis, as well as ATP content after the mitochondria were introduced into the melanoma cell media. The results exhibited that both pyruvate and lactate levels were reduced, accompanying with decreases of ATP content in the mitochondria-treated cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since tumor cells produce energy through aerobic glycolysis (Warburg Effect) under hypoxia condition 12 , 13 , we examined the levels of pyruvate and lactate, the metabolites of glycolysis, as well as ATP content after the mitochondria were introduced into the melanoma cell media. The results exhibited that both pyruvate and lactate levels were reduced, accompanying with decreases of ATP content in the mitochondria-treated cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that increasing evidence implicate altered DNA methylation in the pathophysiology of gestational diabetes mellitus (GDM) ( El Hajj et al, 2013 ; Reichetzeder et al, 2016 ; Dias et al, 2019 ) and a possible general defect in DNA methylation in diabetes is suggested ( Maier & Olek, 2002 ; Enquobahrie et al, 2015 ). WWOX gene is classified among the differentially methylated T2D susceptibility genes in adipose tissue ( Nilsson et al, 2014 ) and one of the targets of DNA methylation affecting the Warburg effect ( Zhu et al, 2020 ). Recent reports point to an important role of WWOX as one of the differentially expressed genes (DEGs) in pancreatic, muscle, and adipose tissue in type 2 diabetics, simultaneously overlapping with the subnetwork of genes responsible for insulin secretion and insulin activity, measured by HOMA- β and HOMA-IR, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation has been described of specific key components in glycolytic pathways, glycolysis bypass pathways (i.e. gluconeogenesis and pentose phosphate pathway), as well as mitochondrial and oxygen sensing pathways ( 66 ). Furthermore many of the intermediates of cellular metabolic pathways participate in the chemical modifications that epigenetically modify DNA and histones ( 67 ).…”
Section: Epigenetic Changes In Tumors That Promote the Warburg Effectmentioning
confidence: 99%
“…Within the tumor, DNA methylation affects key glycolytic components, including glucose transporters (GLUT1, GLUT3), lactate dehydrogenase genes ( LDH-A, LDH-B ), the hexokinase 2 isoform (HK2), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), and the pyruvate kinase (PK) isoform M2 (PKM2), each of which contribute to the Warburg effect ( 66 ). DNA hypermethylation-mediated inactivation of the Derlin-3 gene, which normally contributes to GLUT1 degradation, leads to increased GLUT1 expression ( 70 ).…”
Section: Epigenetic Changes In Tumors That Promote the Warburg Effectmentioning
confidence: 99%
See 1 more Smart Citation